2021
DOI: 10.2516/ogst/2021038
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen compounds removal from oil-derived middle distillates by MIL-101(Cr) and its impact on ULSD production by hydrotreating

Abstract: Oil-derived middle distillates (straight-run gas oil and mixture with light cycle oil and coker gas oil) for Ultra-Low Sulfur Diesel (ULSD) production by HyDroTreating (HDT) were pretreated by selective Nitrogen Organic Compounds (NOC) adsorption. Highly crystalline Metal-Organic Framework (MOF) MIL-101(Cr) prepared with propylene oxide (proton scavenger) as textural improver was used to that end. MOF was characterized by N2 physisorption, X-ray diffraction, thermal analysis, infrared, Raman and UV-vis spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Many studies have been conducted to improve the ultradeep HDS performance of the middle distillates. , It has been found that the coexisting organic nitrogen compounds, such as aniline, pyridine, quinoline, acridine, indole, carbazole, and their derivatives, in the liquid hydrocarbon streams, even at very low concentrations, strongly poison the hydrotreating catalysts by competitive adsorption on the active sites of the catalyst, and thus significantly inhibit the deep HDS of the middle distillates for producing ULSD. It has been reported in the literature that the removal of these nitrogen compounds from feedstock prior to deep HDS could remarkably improve the deep HDS performance. Furthermore, the nitrogen compounds in fuels cause odor and color and reduce the thermal and oxidative stability of fuels . Consequently, deep denitrogenation of liquid hydrocarbon streams for producing ultraclean fuels is becoming an increasingly important research subject worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have been conducted to improve the ultradeep HDS performance of the middle distillates. , It has been found that the coexisting organic nitrogen compounds, such as aniline, pyridine, quinoline, acridine, indole, carbazole, and their derivatives, in the liquid hydrocarbon streams, even at very low concentrations, strongly poison the hydrotreating catalysts by competitive adsorption on the active sites of the catalyst, and thus significantly inhibit the deep HDS of the middle distillates for producing ULSD. It has been reported in the literature that the removal of these nitrogen compounds from feedstock prior to deep HDS could remarkably improve the deep HDS performance. Furthermore, the nitrogen compounds in fuels cause odor and color and reduce the thermal and oxidative stability of fuels . Consequently, deep denitrogenation of liquid hydrocarbon streams for producing ultraclean fuels is becoming an increasingly important research subject worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches have been employed in recent years by using nonhydrotreating processes for removing the nitrogen compounds from middle distillates, including liquid–liquid extraction denitrogenation (L/L-EDN), ADN, oxidative denitrogenation (ODN), and others. , ADN has shown high efficiency and promise in removing nitrogen compounds from fossil fuels due to its nature, low cost, environmental friendliness, and sustainability. , The process is a favorable nitrogen reduction pathway as it can operate at very mild conditions without consuming hydrogen gas. Furthermore, it would be highly favorable to develop an optimal pretreating ADN process to remove nitrogen compounds selectively and thus improve the HDS reactivity of feedstock and enhance the overall performance of the existing hydrotreating unit.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations